Functional Programming Using the New C++ Standard - Bucea-Manea-Tonis, Radu; Tonis (Bucea-Manea), Rocsana (Journal of Economic Development, Environment and People, 2015)
Today software technology evolves very quickly, to an old paradigm, called functional programming. This paradigm uses lambda functions ready to be used where declared instead of function pointers. The long term target is to let compilers evaluate rather than execute a program/function. The new C++14 standard allows lambda calculus as we demonstrate in the applicative section of implementing conditionals, booleans and numbers.